2017
DOI: 10.1158/2159-8290.cd-16-1049
|View full text |Cite
|
Sign up to set email alerts
|

Combination Targeted Therapy to Disrupt Aberrant Oncogenic Signaling and Reverse Epigenetic Dysfunction in IDH2- and TET2-Mutant Acute Myeloid Leukemia

Abstract: Genomic studies in acute myeloid leukemias (AML) have identified mutations which drive altered DNA methylation, including TET2 and IDH2. Here we show that models of AMLs resulting from TET2 or IDH2 mutations combined with FLT3ITD mutations are sensitive to 5-Azacytidine or to the IDH2 inhibitor AG-221, respectively. 5-Azacytidine and AG-221 treatment induced an attenuation of aberrant DNA methylation and transcriptional output, and resulted in a reduction in leukemic blasts consistent with anti-leukemic activi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 47 publications
(50 reference statements)
6
101
0
Order By: Relevance
“…Moreover, new single-base resolution methods are also emerging, which can leverage regional, phased, and long-range information from differentially methylated regions, single molecule sequencing, and new nanopore-based methods [2830]. Notabl, y these techniques are already leading to new combined therapies and measure in leukemia patients with specifical mutations, like DNMT3A and TET mutations [3132]. But beyond improving the reliability and accuracy of these low-input methods (which often involve extensive PCR or signal amplification), there is an ongoing debate about the applicability of these methods for improving clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, new single-base resolution methods are also emerging, which can leverage regional, phased, and long-range information from differentially methylated regions, single molecule sequencing, and new nanopore-based methods [2830]. Notabl, y these techniques are already leading to new combined therapies and measure in leukemia patients with specifical mutations, like DNMT3A and TET mutations [3132]. But beyond improving the reliability and accuracy of these low-input methods (which often involve extensive PCR or signal amplification), there is an ongoing debate about the applicability of these methods for improving clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] In preclinical studies, enasidenib (AG-221/CC-90007), a small-molecule inhibitor of mIDH2, reduced serum 2-HG, DNA hypermethylation, and repressive histone marks and promoted hematopoietic differentiation in R140 and R172 mIDH2 models. [14][15][16][17] In a phase 1/2 clinical trial, enasidenib demonstrated clinical activity in patients with both R140 and R172 mIDH2 relapsed/refractory AML (rrAML) with an overall response rate (ORR) of 40.3%. 18 Here, we analyzed samples from this study to elucidate the mechanisms of action of enasidenib in R140 and R172 mIDH2 rrAML patients and to identify response biomarkers to targeted mIDH2 therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although intensive efforts have been made to investigate the cellular functions of IDH-mutant derived D-2HG, and a selective, potent inhibitor of mutant IDH2, AG-221, was shown to be effective in IDH2 mutation-positive acute myeloid leukemia (55,56), its mirrorimage enantiomer L-2HG is less understood. Interestingly, recent studies found that hypoxia dramatically induces production of L-2HG in both normal and malignant cells (57,58).…”
Section: L-2-hydroxyglutarate (L-2hg) Production and Functionmentioning
confidence: 99%